The Educational Reality in Al-Samawa District and Its Impact on Religious and Cultural Diversity, 1921–1945 - Mustafa, Assoc. Prof. Dr. Ali Ibrahim Mohammed Mustafa; Mustafa, Assoc. Prof. Dr. Ahmed Ibrahim Mohammed Mustafa (Sulaimani Journal for Humanities, 2026)
Historical writings up to the first quarter of the twentieth century focused on documenting history through a positivist methodology, as outlined by the traditional school. This school was grounded in the principle that "there is no history without documentation," viewing history primarily as political developments verified solely by written records. Its main focus was on wars, revolutions, and governments, thus narrowing history’s role to the affairs of power, reducing the historian’s task to chronicling authority. However, the French Annales School emerged with a broader perspective, emphasizing causes before outcomes. This shift led to a focus on societies and their economies as engines, vessels, and guides for political developments. The historian's role evolved toward studying "history from below," emphasizing the need to investigate societal aspects, particularly education. Based on this perspective and the research title, several questions arise: When did the society in Al-Samawa begin to regard education as a vital necessity? What was the impact of authority on this perception? Did non-Muslim religions participate in government schools established by the authorities? How did these schools contribute to producing human capital that played a pioneering role in Iraq’s political and cultural history? Seeking answers to these questions required dividing the study into two main sections. The first section, titled “The Educational Reality in Al-Samawa between Government Policy and Societal Needs, 1921–1928,” addresses the education policies of the authorities, the impact of the British Mandate on these policies, the national education system, the primary schools established in Al-Samawa district, the social and religious composition of their attendees, and the issue of curricula inadequately meeting societal needs. The second section, “Attempts to Reform the Educational Reality in Al-Samawa District, 1929–1945,” highlights the supervisory role of the authorities and their efforts to develop infrastructure supporting education, as well as efforts to improve the teaching staff. It particularly emphasizes the role of the “Heavenly Families” (the Jewish community) in staffing schools with personnel from their own society, who understood the behavior and desires of their community members. The research concludes with a series of findings summarizing the core insights drawn from the study. It relies heavily on primary and secondary sources, with documents providing the main evidentiary foundation. Oral histories were also incorporated due to their importance in reading historical developments from the perspective of the common people, which constitutes the fundamental goal of the study.
Keywords: AlSamawa; Education; District; School; Annals; Minorities